Acyclic Diene Metathesis (ADMET) Polymerization of 2, 2, 6, 6‐Tetramethylpiperidine‐1‐sulfanyl (TEMPS) Dimers. Issue 10 (8th April 2021) - Hobich, Jan; Huber, Birgit; Theato, Patrick; Mutlu, Hatice
Abstract: The preparation of polymers containing sulfur–nitrogen bond derivatives, particularly 2, 2, 6, 6‐tetramethylpiperidine‐1‐sulfanyl (TEMPS) dimers (i.e., BiTEMPS ), has been limited to free‐radical or conventional step‐growth polymerization as result of the inherent thermal lability of the BiTEMPS unit. Accordingly, a novel poly(diaminodisulfide) possessing the BiTEMPS functional group is synthesized via acyclic diene metathesis (ADMET) polymerization at 65–75 °C within 3 h with precise control over the primary polymer structure. Polymer is isolated with an M n of 20 400 g mol −1 and Ð of 1.9. Importantly, detailed nuclear magnetic resonance (NMR), size exclusion chromatography, attenuated total reflectance Fourier transform infrared (ATR‐IR) in addition to elemental analysis studies of the BiTEMPS polymer confirm the successful polymerization, and show that the BiTEMPS unit remains intact during the polymerization process. Furthermore, the previously unexplored UV‐responsiveness of the BiTEMPS decorated polymer backbone is investigated for the very first time. Abstract : A novel poly(diaminodisulfide) possessing the BiTEMPS functional group is synthesized in a straightforward fashion via acyclic diene metathesis (ADMET) polymerization. The previously unexplored UV‐responsiveness of the BiTEMPS decorated polymer backbone is also investigated for the very first time.